Long non-coding HCG18 promotes intervertebral disc degeneration by sponging miR-146a-5p and regulating TRAF6 expression. Issue 1 (December 2017) - Xi, Yanhai; Jiang, Tingwang; Wang, Weiheng; Yu, Jiangming; Wang, Yang; Wu, Xueming; He, Yunfei
Abstract Intervertebral disc degeneration (IDD) is associated with the deterioration of nucleus pulposus (NP) cells due to hypertrophic differentiation and calcification. Emerging studies have shown that long noncoding RNAs (lncRNAs) play critical roles in the development of IDD. Using bioinformatics prediction, we hereby sought to identify the lncRNAs that regulate the expression of microRNA-146a-5p (miR-146a-5p), an IDD-related inflammatory factor. Our study demonstrated that lncRNA HCG18 acted as an endogenous sponge to down-regulate miR-146a-5p expression in the NP cells by directly binding to miR-146a-5p. In addition, HCG18 expression was up-regulated in the patients with IDD, bulging or herniated discs, and its level was positively correlated with the disc degeneration grade.In vitro, miR-146a-5p up-regulation HCG18 retarded the growth of NP cells by decreasing S phase of cell cycle, inducing cell apoptosis, recruitment of macrophages and hypercalcification. Conversely, down-regulation of miR-146a-5p exerted opposite effects. Furthermore, we elucidated that TRAF6, a target gene by miR-146a-5p, was modulated by HCG18 expression. Restore of TRAF6 expression by virus infection reserved the effect of HCG18 on the NP cells. Altogether, our data indicated that HCG18 suppressed the growth of NP cells and promoted the IDD development via the miR-146a-5p/TRAF6/NFκB axis.